Synthesis and Characterization of Magnetic Molecularly Imprinted Polymers Targeting Capsaicin - Amri, Ahmad Mukhlasul; Azis, Muhammad Yudhistira; Zulfikar, Muhammad Ali (Syarif Hidayatullah State Islamic University, 2024)
A novel magnetic molecularly imprinted polymers (MMIPs) was developed for the adsorption of capsaicin, a key component of capsaicinoids widely used in food additives and topical pharmaceuticals. Excessive use of capsaicin can lead to respiratory, skin, and oral disorders, necessitating effective monitoring methods. This study aimed to synthesize MMIPs and magnetic molecularly non imprinted polymers (MNIPs) using 4-vinyl pyridine as the functional monomer and ethylene glycol dimethacrylate (EGDMA) as the crosslinker, combined with an initiator in a 1:4:20 molar ratio. Magnetite nanoparticles (Fe3O4) were incorporated to facilitate magnetic separation. Characterization via particle size analyzer (PSA), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) confirmed the successful synthesis of Fe3O4 nanoparticles, MNIPs, and MMIPs. PSA analysis for Fe3O4 nanoparticles showed an average size of 140.2 nm with a polydispersity index (PI) of 0.313, MMIPs showed an average particle size of 746.6 nm and a PI value of 0.397. FTIR spectra revealed characteristic absorption bands at 3429 cm−1 (O-H), 2958 cm−1 (C-H), 1732 cm−1 (C=O), 1155 cm−1 (C-O), and 580 cm−1(Fe-O), indicating successful Fe3O4 modification. SEM-EDS analysis showed non-spherical morphology due to bulk polymerization. TEM image results showed Fe₃O₄ nanoparticles were successfully coated with a molecularly imprinted polymer (MIP). The developed MMIPs effectively have a robust synthesis method and thorough analysis, laying the groundwork for future applications.